Toxic stress and its influence on childhood and adolescence during the COVID-19 pandemic: a comparison in public and private schools in the municipality of Paulo Afonso-BA (Research, Society and Development, 2022)
Objective: to evaluate the impact of the COVID-19 pandemic as a triggering factor of toxic stress in childhood, which areas have undergone the greatest changes, and to make a comparison of the impact of this period on children from different social classes. Methodology: application of online questionnaires to parents or guardians of children, in schools in the city of Paulo Afonso-BA. Results: it was found that with advancing age, children and adolescents were 6.8 times more likely to manifest a negative change in routine during the pandemic period; also, public school students were 5.58 times more likely to be negatively affected for that moment. Conclusion: The present article demonstrated the negative impact generated by the COVID-19 pandemic on the health of children and adolescents in the city of Paulo Afonso-BA, disproportionately affecting those enrolled in public institutions and with more advanced ages. It was possible to identify the association between the drop in school performance with introspection and the interruption of physical exercise in this population. The need to invest in further studies on the subject becomes evident.